Synthesis and chelation study of a fluoroionophore and a glycopeptide based on an aza crown iminosugar structure. (March 2021) - Bordes, Alexandra; Poveda, Ana; Fontelle, Nathalie; Ardá, Ana; Guillard, Jérôme; Ruan, Yi Bin; Marrot, Jérôme; Imaeda, Shuki; Kato, Atsushi; Désiré, Jérôme; Xie, Juan; Jiménez-Barbero, Jesús; et al.
Abstract: Capitalizing on a recently reported iminosugar-based aza-crown (ISAC) accessed by a double Staudinger azaWittig coupling reaction, we have expanded the structural diversity of this new family of sweet cyclam analogs. Replacement of the two secondary amines linking the iminosugar units by two amide bonds obtained a cyclodimerization by with BOP and DIPEA led to a macrocycle that did not demonstrate efficient Zn 2+ chelation unlike the parent ISAC. Introduction of two pyrene moieties on the secondary amines of the parent ISAC yielded a new fluoroionophore that selectively binds Hg 2+ in methanol. Graphical abstract: Image 1 Highlights: First synthesis of fluoroionophore based on an iminosugar scaffold. The fluoroionophore shows selectivity for Hg ++ cations. First synthesis of iminosugar azacrown (ISAC) with amide pending arms. Introduction of amide arms abolishes the chelation properties observed for ISAC with amine arms.